How do you solve 3x + 4y = 4 and 2x + y = 6?
The answer would be (4, -2)
We can use substitution to solve this problem.
Let's use the second equation and manipulate it to be equal to y:
We can then plug in this value for the y value in the first equation, getting the following:
#3x + 4(6-2x) = 4#
Then we can simplify that equation to equal this;
#24 - 5x = 4#
Then we can solve for the x value,
We can then plug 4 in for x into the other equation
This shows that y is -2. The point is therefore (4, -2). We can check this by plugging it into the original equations.